Implementation of Good Governance in Improving Consular Services at the Consulate General of the Republic of Indonesia in Tawau - Agussalim Agussalim; Amirul Mustofa; Sarwani Sarwani; Dian Ferriswara (International Journal of Humanities and Social Sciences Reviews, 2026)
This study analyzes the implementation of Good Governance in enhancing consular services at the Consulate General of the Republic of Indonesia in Tawau, using a qualitative approach with a case study paradigm. The findings reveal several key points: First, transparency in consular services is achieved through openness about procedures, fees, and service time standards via official platforms like websites, social media, and notice boards. This transparency reduces information asymmetry, prevents maladministration, and builds trust. Second, service accountability is reflected in the timely execution of passport renewals, Emergency Travel Documents, and document legalization, following Standard Operating Procedures (SOPs). Accountability is further demonstrated through performance reports, complaint channels, and service evaluations. Third, public participation is fostered through two-way communication, complaint mechanisms, and collaboration with Indonesian citizen and migrant worker communities. The mobile consular service program also enhances accessibility. Finally, consular services are based on clear legal frameworks, ensuring the legitimacy of services and protection for Indonesian citizens and migrant workers. Overall, the study concludes that the implementation of Good Governance principles at the Consulate General of Indonesia in Tawau significantly improves the quality of consular services.